Kinesin Eg5 Targeting Inhibitors as a New Strategy for Gastric Adenocarcinoma Treatment - Guya Diletta Marconi; Simone Carradori; Alessia Ricci; Paolo Guglielmi; Amelia Cataldi; Susi Zara (Molecules, 2019)
The Kinesins are proteins involved in several biological processes such as mitosis, intracellular transport, and microtubule movement. The mitotic process is allowed by the correct formation of the mitotic spindle which consists of microtubules originating from the spindle poles. In recent years, kinesin Eg5 inhibitors were studied as new chemotherapeutic drugs, due to the lack of side effects and resistance mechanisms. The aim of this work was to investigate the molecular signaling underlying the administration of novel kinesis Eg5 inhibitors in an in vitro model of gastric adenocarcinoma. Data obtained from analogues of K858 led us to select compounds 2 and 41, due to their lower IC50 values. The ability of kinesin inhibitors to induce apoptosis was investigated by evaluating Bax and Caspase-3 protein expression, evidencing that compound 41 and K858 markedly raise Bax expression, while only compounds 2 and 41 co-administrated with K858 trigger Caspase-3 activation. The inhibition of mitotic spindle was measured by β-tubulin immunofluorescence analysis revealing monopolar spindles formation in gastric cancer cells treated with compounds 2, 41, and K858. Nitric Oxide Synthase (NOS-2) and Matrix Metalloproteinase 9 (MMP-9) expression levels were measured finding a NOS-2-mediated downregulation of MMP-9 when compound 41 and K858 are co-administered. However, this is in contrast to what was reported by migration assay in which both novel compounds and K858 in monotherapy markedly reduce cell migration. This work remarks the importance of understanding and exploring the biological effects of different novel Eg5 kinesin inhibitors administered in monotherapy and in combination with K858 as potential strategy to counteract gastric cancer.